PELAKSANAAN PERJANJIAN PEMBIAYAAN MULTIGUNA KENDARAAN BERMOTOR RODA EMPAT DENGAN JAMINAN FIDUSIA DI PT. INTERNUSA CITRA MULTIFINANCE - Boby Harisma Raharja; Nurhidayah (Constitutum: Jurnal Ilmiah Hukum, 2024)
The increase in public mobility has driven the demand for four-wheeled motor vehicle loans from financing companies. Based on fiduciary agreements, there are several issues, including non-performing loans or defaults on the agreed contracts. The implementation of multipurpose financing agreements at PT. Internusa Tribuana Citra Multifinance involves procurement activities.Debtors apply for multipurpose financing facilities. The pre-agreement stage includes administrative requirements, installment amounts, and down payments. Once the parties agree to use fiduciary collateral, a standard agreement is created. The documents that the debtor needs to sign during the financing agreement process at PT. Internusa Tribuana Citra Multifinance include the Multipurpose Financing Agreement Form, Credit Approval, spouse’s approval, insurance form, a statement that the debtor will notdefault, and approval for the repossession of the fiduciary collateral in case of default. These documents are validated, and then a notarial deed is created and registered at the Fiduciary Registration Office. The creditor receives a fiduciary certificate, as its legal strength is equivalent to a court decision with permanent legal force. The resolution of defaulting debtors at PT. Internusa Tribuana Citra Multifinance is initially pursued through peaceful means, using negotiation and familial procedures. If these efforts fail, the finalrecourse is through legal channels, executing the collateral pledged to the creditor.